A Due Process Right to Record the Police - Glenn Harlan Reynolds; John A. Steakley (Washington University Law Review, 2012)
Do citizens have a right to record the actions of law enforcement officers? This topic has been the subject of considerable discussion, and no small degree of litigation, in recent years. The increase in litigation is driven by dramatic improvements in camera technology, which allow individuals to record and share images in ways that were previously available, if at all, only to members of large media organizations. Most of the discussion and litigation has revolved around the question of whether there is a First Amendment right to record police officers in public. In the recent First Circuit case of Glik v. Cunniffe, for example, passerby Simon Glik caught sight of three police officers arresting a young man. Hearing a passerby shout that the officers were hurting the man, Glik turned on his cell phone and began capturing video. The police officers objected to being recorded, arrested Glik and charged him with violating the state’s “wiretap” law by recording them without their consent, and seized his camera and memory chip in the process as evidence. The First Circuit held that the right to record police officers in public is a “clearly established” part of the First Amendment’s protections, and held the officers were not entitled to qualified immunity. Though the issue has not yet reached the Supreme Court, it seems safe to say that the case for First Amendment protection regarding photos and video of law enforcement officers in public is quite strong, and is in the process of being resolved. This Article, however, argues that independent of any First Amendment right, there is also a due process right to record the actions of law enforcement, and that this right applies even when the interaction takes place in private, and not in public places. This question of a due process right to record the police has not yet produced the degree of attention and litigation that public recording has, but the growth of inexpensive recording equipment and its inclusion in smart phones ensures that such attention and litigation are sure to be forthcoming.